An Analisis of @ajobendri’s Communication Style in Parenting Educatuonal Content on Instagram - hasfi, wirda tri; Mau, Muliadi; Farid, Muhammad; Ng, Khar Thoe (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2023)
The best instrument a communicator has for influencing the communicant is their communication style. The style of communication has grown increasingly important, especially for content creators, thanks to the advancement of information technology and the existence of social media, which makes it simpler for people to connect on a single platform. The purpose of this study was to determine the communication style of the Instagram account @ajobendri in providing parenting education. Primary data for this study came from observations made on the social media platform Instagram @ajobendri, as well as from pertinent books, journals, and findings from other studies. This research is a qualitative research using phenomenological methods. According to the findings of the study, the Norton concept of communication is dramatic, i.e., with sound play and diction, animated expressive, i.e., with facial expressions and gestures, open, i.e., with an attitude that encourages two-way communication, impression leaving, i.e., with the capacity to make an impression on his listeners, relaxed, i.e., with the capacity to be upbeat and friendly, and friendly.